Contributions to the biophilosophical foundations of brain death criterion: an approach from anthropological realism - Sergio Götte (Revista de Bioética y Derecho)
This article analyzes from a biophilosophical point of view whether it is advisable to adjust the current brain death criteria, according to recent discoveries about brain function. The appropriate foundation for a death criterion is recognizing that a human being is more than his or her physical aspect, within which the brain plays a decisive role. Current neurology states that the brain functions globally. Thus, the irreversible loss of integrated brain activity indicates the end of the irreplaceable function performed by the brain to sustain the unity of the organism. Consequently, the function cessation of the brain-as-a-whole is an adequate adjustment of the brain death criterion. To be recognized as a legitimate criterion from a philosophical point of view and to provide a better framework for the development of laws, the death criterion must presuppose a comprehensive anthropological vision that considers all dimensions of the human being.